Analisis Kekuatan Tarik Sambungan Las Kombinasi Smaw-Gtaw Pada Pipa Carbon Steel A106 Grade B - Novan Dwi Prasetyo (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the tensile strength of SMAW-GTAW combination welds on ASTM A106 Grade B carbon steel pipes. This material is widely used in oil and gas pipeline industries because of its good mechanical properties and ability to withstand high pressure and temperature. The research method used was an experimental method with tensile testing using the LLOYD LR150K Tensile Testing Machine. The welding process was carried out using SMAW for the root pass and GTAW for the filler and capping passes in the 6G welding position. The test results showed an average yield stress of 385.3 MPa, ultimate tensile strength (UTS) of 514.7 MPa, and fracture strength of 496.4 MPa. These values are higher than the minimum tensile strength standard of ASTM A106 Grade B, which is 415 MPa. Visual observations also showed that both specimens experienced ductile fracture, indicated by plastic deformation and necking before fracture occurred. Therefore, the SMAW-GTAW combination welding method produced good weld quality and mechanical strength suitable for pressurized piping applications.